Pengaruh tepung mocaf terhadap penambahan tepung seledri pada produk pangan fungsional crackers - Husna, Ella Syauqa; Purwani, Eni (TEKNOLOGI PANGAN : Media Informasi dan Komunikasi Ilmiah Teknologi Pertanian, 2026)
Crackers made from mocaf flour are a local food-based snack alternative that can reduce dependence on wheat flour; however, they have relatively limited nutritional content, particularly in terms of protein and micronutrients. The addition of celery flour is expected to enhance the nutritional value of the product because it contains vitamin C, dietary fiber, and bioactive compounds that are beneficial to health. This study aims to determine the effect of adding celery flour on the levels of vitamin C, dietary fiber, and protein in product crackers made from mocaf flour. Crackers were formulated with 0%, 3%, 6%, and 9% celery flour, and then analyzed for vitamin C content, total dietary fiber, soluble fiber, insoluble fiber, and protein using laboratory testing methods. The data obtained were statistically analyzed using a one-way ANOVA test, followed by Duncan’s multiple range test to determine differences among treatments. The results of the study showed that increasing the percentage of celery flour led to a significant increase in vitamin C, dietary fiber, and protein content. The highest values were obtained with a 9% addition of celery flour, with a vitamin C content of 24.30 mg, total dietary fiber of 5.98%, and protein of 3.34%. Additionally, acceptability tests indicated that the product remained acceptable to panelists up to a certain level of addition, although increasing the concentration of celery flour tended to reduce the level of preference regarding taste and texture. These results indicate that the addition of celery flour can improve the nutritional quality of crackers made from mocaf and has the potential to be developed as a functional food with enhanced nutritional value.